A argumentação nos livros didáticos de língua portuguesa para o ensino médio: uma concepção retórica ou linguística? - Costa, Thiago magno de carvalho (2015)
Considering that the official documents, PCN (1997), PCNEM (2000), PCN + (2002) and OCEM (2006), not clearly prescribe under which argumentative perspective (if rhetorical or linguistic) the teacher should work, this research took as its starting point the assertion that the Portuguese language textbooks tend to approach a more rhetorical aspect about argumentation. In addition, we started with the assumption that the linguistic aspects, according to the Theory of Argumentation within Language, developed by Oswald Ducrot (1987, 1988) and collaborators, may be relevantly designed and used in the classroom. As it is a qualitative-interpretative research of documentary and exploratory scope, we hope to contribute to linguistic researches, with a theoretical approach in studies of genres and the Semantic Argumentative as well as the analysis of textbooks, in order to identify if and how the rhetorical and semantic-argumentative strategies and resources support the activities concerning the argumentation proposed by four collections of Portuguese language textbooks, evaluated by the National Textbook Program (PNLD, 2012), adopted in ten public high schools in the city of João Pessoa, PB. In this sense, according to seven categories of analysis (four for rhetoric argumentation and three for linguistic argumentation), it was intended to check which conception the textbook authors used when preparing their activities about argumentative strategies based on two genres: opinion article and argumentative letter. During the research, we tried to make it clear that both rhetorical (ARISTOTLE, 2005; PERELMAN, 1999) and linguistic (DUCROT, 1987, 1988) aspects should be worked simultaneously in mother tongue classes. In addition to the description and analysis of the activities of textbooks, we proposed, as a suggestion and reflection, in the final chapter, two complementary activities in accordance to Linguistic Analysis in an attempt to show the need of working the argumentative strategies within the classroom and try to bridge the gap between what is prescribed in the official documents and what is actually taught to students. We based the analysis with the theoretical support of Aristotle (2005), Perelman (1999) Ducrot (1987, 1988, 2009), Nascimento (2005, 2009, 2012), Koch (2000, 2003, 2004, 2011), Espíndola (1998, 2004), Cabral (2010), Marcucshi (2002, 2003, 2008), Geraldi (1984), among others.